2017
DOI: 10.3390/children4080072
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Sleep in Children with Autism Spectrum Disorder

Abstract: Sleep disturbances in children with autism spectrum disorder (ASD) are significantly more prevalent than found in typically developing (TD) children. Given the detrimental impact of poor sleep on cognitive, emotional, and behavioral functioning, it is imperative to screen and assess for sleep disturbances in this population. In this paper, we describe the screening and assessment process, as well as specific measures commonly used for assessing sleep in children with ASD. Advantages and limitations for use in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 128 publications
2
48
0
3
Order By: Relevance
“…Sleep disturbances appear in 40-80% of children with ASD [2][3][4][5] , as compared with 20-40% of typically developing children 6,7 . Symptoms include prolonged sleep latency, shorter sleep duration, and increased wake periods during the night, as reported by both subjective parental questionnaires and actigraphy measures [8][9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Sleep disturbances appear in 40-80% of children with ASD [2][3][4][5] , as compared with 20-40% of typically developing children 6,7 . Symptoms include prolonged sleep latency, shorter sleep duration, and increased wake periods during the night, as reported by both subjective parental questionnaires and actigraphy measures [8][9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the most prevalent sleep problems indicated in individuals with developmental disabilities are in the "insomnia" category. The current data demonstrates that these problems are generally behavioral problems that cause the individual to sleep less such as resistance to going to bed/sleep, difficulty to sleep, sleeping together, waking up at night, waking up very early in the morning (Moore, Evans, Hanvey and Johnson, 2017). The causes of sleep problems can vary and are influenced by biological, developmental, psychological, environmental and cultural factors.…”
Section: Sleep Problems In Individuals With Developmantal Disabilitiesmentioning
confidence: 81%
“…Sleep questionnaires are used for providing information from the parents for their children's sleep behaviors. It gives data about sleeping problems as resistance to sleep, sleep onset delay, early waking, night waking, sleep terror, parasomnia, sleep duration, bedtime routines, bedtime habits and parent behaviors (Moore et al, 2017). One of that surveys is Children's Sleep Habits Questionnaire (CSHQ) and brief Turkish form of CSHQ's validity and reliability analysis were studied by Perdahlı Fiş and her colleagus (2010).…”
Section: Assessment Of Sleeping Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although objective measures provide more diagnostic evidence, determining different sleep variables, however, these methods have several limitations which make them less practical in clinical settings and in large clinical research trials, such as dependence on the applying of devices or equipment that may malfunction, being expensive, need expert data download and interpretation, and being uneasy or onerous to children at bedtime, especially for autistic children who exhibit sensory difficulties. In addition, polysomnography is commonly conducted in laboratory situations and has not yet been extensively approved in paediatric research and practice [10]. Interdevice reliability was also found to be poor [11]; therefore, results will not be compared among studies that have used different devices [12].…”
Section: Subjective or Objective Measures Of Sleep Disorder?mentioning
confidence: 99%